2011
DOI: 10.1007/s00253-011-3647-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of rRNA group I pseudomonads in contaminated metalworking fluids and biofilm formation by fluorescent in situ hybridization

Abstract: Metalworking fluids (MWFs), used in different machining operations, are highly prone to microbial degradation. Microbial communities present in MWFs lead to biofilm formation in the MWF systems, which act as a continuous source of contamination. Species of rRNA group I Pseudomonas dominate in contaminated MWFs. However, their actual distribution is typically underestimated when using standard culturing techniques as most fail to grow on the commonly used Pseudomonas Isolation Agar. To overcome this, fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Pseudomonas fluorescens was visualized using probe Pseudo120 labelled with a 6‐FAM fluorophore (Saha et al . ). To visualize E. tracheiphila , we designed a species‐specific probe.…”
Section: Methodsmentioning
confidence: 97%
“…Pseudomonas fluorescens was visualized using probe Pseudo120 labelled with a 6‐FAM fluorophore (Saha et al . ). To visualize E. tracheiphila , we designed a species‐specific probe.…”
Section: Methodsmentioning
confidence: 97%
“…Due to the continuous release of microbial biomass from biofilm sources, there exists a steady concentration of microorganisms (10 7 CFU/ml) capable of growth (within 12 h after cleaning; Veillette et al 2004), which makes control application critical in MWF systems with biofilms (Skerlos et al 2001). A recent study by Saha et al (2011b) demonstrated that, under a low concentration of cells, biofilm formation (Fig. 3) by some of the predominant species of Pseudomonas could be delayed by 24 h, indicating that implementation of suitable disinfection methods along with a proper fluid management system could prolong the life of in-use MWFs.…”
Section: Biofilmmentioning
confidence: 98%
“…The BactiFluor method was performed successfully in all the 107 MWF samples used along with 30 other metal-processing fluids. Saha et al (2011b) also developed a FISH method for the rapid detection of rRNA group I pseudomonads in contaminated MWFs and to study the biofilm-forming capabilities of some of the predominant Pseudomonas species. The unique Pseudo120 probe successfully detected and enumerated the abundance and distribution of Pseudomonas, indicating levels between 3.2 (± 1.1)×10 6 and 5.0 (± 2.3)×10 6 cells/ml of used MWFs.…”
Section: Applications Of Fishmentioning
confidence: 99%
“…The number of the publications on biofilms growing in the MWFs environment is limited. In a recent work [41], the biofilms formed by Pseudomonas isolates were grown on microscope slides and FISH technique was used to evaluate which species of the bacteria was actually forming the biofilm. This technique allowed the detection of live bacteria in the biofilms, both grown in the laboratory, as well as these existing in the coolant samples collected from industrial plants.…”
Section: Biofilmmentioning
confidence: 99%